How to challenge university students to work on integrated reporting and integrated reporting assurance - Rodrigues, Maria Albertina Barreiro (2021)
Since the beginning of the twenty-first century, society has become more sensitive to sustainability and to the consequences of companies’ activities. Furthermore, the demands for change in corporate reporting have led to the emergence of integrated reporting (IR) and an increase in the disclosure of nonfinancial information assurance to ensure the compliance of integrated information. Universities need to embrace this challenge and be part of this change. This research’s goal is to enhance the diffusion of IR and integrated reporting assurance (IRA) in the curricula of universities by presenting a tool for professors and universities to help introduce the subjects in higher education institutions. The methodological approach develops a theoretical analysis of published IR and IRA articles related to education, to create a presentation of the challenge learning method (CLM) for professors and high education institutions to develop the subject of IRA to challenge students. Considering teaching experience as a value-added component to research the proposed method comes from the teaching experience of the authors. The result consists of a method that can increase accounting academics knowledge of IR and IRA and motivate students to study these emerging accounting practices. This study contributes to the extant literature on IR, IRA and Education that is scarce, the use of appropriate teaching methods to IR and IRA, and the dissemination of IR and IRA in education by providing a better connection between the universities and the best practices of corporate reporting and auditing. This study leads to an increase in the connection among higher education institutions, professors, students, practitioners, auditors, regulators, standard setters, and society in general.